Flight of Aquavit - Bidulka, Anthony, 1962- (Bidulka, Anthony, 1962- Russell Quant mystery., 2004)
At the dead end of a desolate country road, a late night meeting suddenly becomes an ambush. Gay private detective Russell Quant is faced with personal threats he can't ignore, a friend who may be a foe and a cagey client with a treacherous monkey on his back. As Quant trails a menacing blackmailer known only as Loverboy, he finds himself immersed in the midnight world of e-dating and parking lot romance. Lured to New York City, Quant tests his wit, wisdom and wiles from the Old World grandeur of Fifth Avenue to the kaleidoscope world of Broadway's electric nightspots. The fast pace continues.